Modern problems of aircraft aerodynamics - Sergey L. Chernyshev (Advances in Aerodynamics, 2019)
Abstract The article represents the discussion of several separate directions of investigations, which are performed by TsAGI flight vehicles aerodynamics specialists at the time. There are some major trends of classical layout of route aircraft and also peculiarities of some prospective flight vehicles. Also there are some hypersonic vehicles aerodynamics questions examined along with problems of creation of civil supersonic transport aircraft. There is a description given for well-known and some newer methods of flow control for drag reduction.